Transient sampling of aggregation-prone conformations causes pathogenic instability of a parkinsonian mutant of DJ-1 at physiological temperature - Milkovic, Nicole M (Protein Sci, 2015)
Various missense mutations in the cytoprotective protein DJ-1 cause rare forms of inherited parkinsonism. One mutation, M26I, diminishes DJ-1 protein levels in the cell but does not result in large changes in the three-dimensional structure or thermal stability of the protein. Therefore, the molecular defect that results in loss of M26I DJ-1 protective function is unclear. Using NMR spectroscopy near physiological temperature, we found that the picosecond–nanosecond dynamics of wild-type and M26I DJ-1 are similar. In contrast, elevated amide hydrogen/deuterium exchange rates indicate that M26I DJ-1 is more flexible than the wild-type protein on longer timescales and that hydrophobic regions of M26I DJ-1 are transiently exposed to solvent. Tryptophan fluorescence spectroscopy and thiol crosslinking analyzed by mass spectrometry also demonstrate that M26I DJ-1 samples conformations that differ from the wild-type protein at 37°C. These transiently sampled conformations are unstable and cause M26I DJ-1 to aggregate in vitro at physiological temperature but not at lower temperatures. M26I DJ-1 aggregation is correlated with pathogenicity, as the structurally similar but non-pathogenic M26L mutation does not aggregate at 37°C. The onset of dynamically driven M26I DJ-1 instability at physiological temperature resolves conflicting literature reports about the behavior of this disease-associated mutant and illustrates the pitfalls of characterizing proteins exclusively at room temperature or below, as key aspects of their behavior may not be apparent.